New Intersections for Student Engagement in Libraries: A Qualitative Exploration of Collaborative Learning with Multimedia Technologies - Webb, Katharine A.; Lu, Tingting; Black, Elizabeth L. (Evidence Based Library and Information Practice, 2008)
Objective – The purpose of this study was to explore new ways librarians can provide meaningful learning experiences for students beyond the traditional classroom assignment and the one-hour library instruction session. Methods – The study was done within a qualitative framework using participative, interpretive, and personal experience methods. The research team consisted of two librarians and a graduate student. Data collected included transcripts of audio-recorded team meetings and interviews, field notes, and a post-project survey, where students described their experiences negotiating the conceptual and technical processes of authoring a multimedia story. The instructional layer was built upon a constructivist approach allowing for a collaborative learning setting to foster learner control and self-efficacy. Results – Findings illustrate the benefits of collaborative approaches for enhancing the learning experiences of students in the library, in this case with multimedia. The data also suggest promising new ways for librarians to facilitate learning and to engage students in the library. Conclusion – Through a multimedia project that involves both librarian-guided exploration and collaborative learning processes, libraries can offer students formal and structured opportunities to explore their own interests or underlying curiosities beyond the classroom assignment and the one-hour library instruction session.